2019
DOI: 10.18203/2319-2003.ijbcp20193135
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of metformin and fenugreek on the lipid profile of type-II diabetic patients

Abstract: Background: Fenugreek is a traditional herb which has great relevance in the world since time immemorial due to its multifarious uses. Besides being a rich source of nutrition, it also finds place in the cure of certain pathological conditions. One of its highly beneficial effects is have been observed on the lipid profile of the hyperlipidemic patient. This study was thus undertaken to see the hypolipidemic effect of fenugreek seeds in patients of Type 2 Diabetes Mellitus (DM) as add-on therapy with metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…This encourages its intake as dietetic supplement to manage the disease and its associated. [36][37][38] In raison of the frequent use of medicinal herbs and unawareness of the general population about their effectiveness, safe doses and toxicological features, some sporadic intoxications have been observed. Ouzir and colleagues (2016) reviewed these properties for fenugreek and found that its LD50 in experimental animals exceeds 3.5 g.kg -1 of body weight.…”
Section: Resultsmentioning
confidence: 99%
“…This encourages its intake as dietetic supplement to manage the disease and its associated. [36][37][38] In raison of the frequent use of medicinal herbs and unawareness of the general population about their effectiveness, safe doses and toxicological features, some sporadic intoxications have been observed. Ouzir and colleagues (2016) reviewed these properties for fenugreek and found that its LD50 in experimental animals exceeds 3.5 g.kg -1 of body weight.…”
Section: Resultsmentioning
confidence: 99%
“…an alarming 300 million cases. These complications include neuropathy, nephropathy, metabolic disorders, retinopathy, weakened defence system and discrepancies in lipid profile and the atherosclerosis, most of them due to the abnormal blood glucose levels 10 . Intricate aetiology of diabetes has thus impacted upon patterns and techniques of management and its medication; from monotherapy to a set of composite and combination therapies.…”
Section: Discussionmentioning
confidence: 99%